The Impact of Pedagogical Agents' Gender on Academic Learning: A Systematic Review - Armando, Marjorie; Ochs, Magalie; Régner, Isabelle (Frontiers in Artificial Intelligence, 2022)
Virtual learning environments often use virtual characters to facilitate and improve the learning process. These characters, known as pedagogical agents, can take on different roles, such as tutors or companions. Research has highlighted the importance of various characteristics of virtual agents, including their voice or non-verbal behaviors. Little attention has been paid to the gender-specific design of pedagogical agents, although gender has an important influence on the educational process. In this article, we perform an extensive review of the literature regarding the impact of the gender of pedagogical agents on academic outcomes. Based on a detailed review of 59 articles, we analyze the influence of pedagogical agents’ gender on students’ academic self-evaluations and achievements to answer the following questions: (1) Do students perceive virtual agents differently depending on their own gender and the gender of the agent? (2) Does the gender of pedagogical agents influence students’ academic performance and self-evaluations? (3) Are there tasks or academic situations which a male virtual agent is better suited to than a female virtual agent, and vice versa, according to empirical evidence? (4) How do a virtual agent’s pedagogical roles impact these results? (5) How do a virtual agent’s appearance and interactive capacities impact these results? (6) Are androgynous virtual agents a potential solution to combatting gender stereotypes? This review provides important insight to researchers on how to approach gender when designing pedagogical agents in virtual learning environments.